Empowering local youth and university students through project-based learning: a case study on incorporating community-based project in the literature classroom - Ahmad, Siti Nuraishah; Md. Zamin, Ainul Azmin (2019)
The study of literature in universities often revolves around analysis of literary texts using various theoretical approaches in order to explore how fiction, poetry and drama address human experience and phenomena such as diaspora, nationalism, transnationalism, dystopia and many others. The emphasis on textual analysis targets cognitive skills but hardly requires students to use and/or acquire other learning skills or strategies. This approach also does not include addressing real-life issues and problems, a role which is expected of universities today. One way of overcoming this is to integrate real-life issues in the literature classroom, to empower both university students and the local community. The aim of this paper is to share the experience of integrating a community-based project in the Women in Asian Literature course, an undergraduate course offered at the Department of English Language and Literature, IIUM. The project required undergraduate students to propose, design and carry out a community-based activity related to the course learning outcomes and one of the United Nations’ Sustainable Development Goals: gender equality. This paper will discuss the processes involved in implementing project-based learning in an undergraduate literature classroom, the assessment methods employed to evaluate students’ contribution to the project, and the students’ experience and responses to project-based learning. Data for this case study were gathered by reviewing the relevant literature on project-based learning and university-community engagement, observations, and student evaluation of the project-based learning element in the course. The community engagement project enabled students of the Women in Asian Literature course to be active learners, communicators and decision makers. As the project owners, they also learned to take the responsibilities that come with the role, work as a team, and build trust with the local community. Most of the participants of the community engagement project were already familiar with gendered roles in society and positive female role models; however, they were not as familiar with the concept of safe and unsafe touch. The incorporation of community engagement via project-based learning enables meaningful learning to take place. By taking the university students outside of the literature classroom and campus and having them engage with local children, they were able to apply their theoretical knowledge of issues explored in literature in a real-life setting. A project-based learning approach to literature diversifies university students’ skills, empowers them and the local children as active learners, and affords the opportunity to build trust with the local community for future collaborations.